The Role of the Cloud in moderating Management Support for the Quality of Hospitality Accounting Information Systems - Dedy Husrizal Syah; Azizul Kholis; Eko Wahyu Nugrahadi; Taufik Hidayat; Gaffar Hafiz Sagala (LP3M Universitas Putra Bangsa, 2023)
The hotel and tourism industry is essential to Indonesia's economy (GDP), especially in North Sumatra, which has the fastest tourist area. The Accounting Information System (SIA) in the hotel industry is beneficial in achieving company goals. Cloud-based SIA integration allows hotels to deliver real-time data so management can access information. This study aims to examine the effect of management support on the quality of SIAs moderated by cloud computing. This study uses quantitative methods by distributing questionnaires. The population in this study is the hotel industry in North Sumatra Province. The sampling technique uses purposive sampling with the criteria of all employees in charge of accounting and financial information systems. The collected data was analyzed using Structural Equational Modelling Partial Least Square (SEM-PLS). The findings obtained from this study showed that management support has a significant positive effect on the quality of accounting information systems, then cloud computing also has a significant positive effect on the quality of accounting information systems, and cloud computing moderates significantly positive relationships between management support and the quality of accounting information systems. The results of this study can be used as recommendations for improving efficiency and accuracy and improving the quality of taking proper business management when an organization implements cloud technology